Upaya Guru Dalam Mengatasi Kesulitan Belajar Siswa Mata Pelajaran Fiqih di SMP Islam Karangploso Malang - Nursya’baniyah Nurdin; Azhar Haq; Khoirul Asfiyak (VICRATINA, 2019)
The teacher is a person who gives knowledge. The teacher is called a professional educator whose job is to design student seating, and establish relationships with parents so that students learning difficulties can be overcome properly. Learning difficulties are vulnerable things eksperienced by students due to certain factors. This is the background of teachers’ efforts in creating an atmosphere that is conducive and confortable for the learning difficulties are not eksperienced by students. The purpose of this study is to describe the learning difficulties of students and the causes of these difficulties and how the teacher mitigates them. To achieve these objectives researchers used a descriptive qualitative research approach. And procedures for collecting data using observation, interviews and documentation. Which is done through 3 stages, namely organizing data and interpreting data.